Next-generation Electrochemical Sensors for Detection of Respiratory Viruses - Akdag, Atakan; Seyman, Dilan; Henry, Charles S.; Sagdic, Osman; Lomae, Atchara; Ruecha, Nipapan; Vilaivan, Tirayut; Chailapakul, Orawon; Ozer, Tugba (MYU, SCIENTIFIC PUBLISHING DIVISION, 2023)
Respiratory viruses have caused many deaths, severe cases, epidemics, and pandemics. Therefore, reliable, rapid, selective, and sensitive detection and quantification of respiratory viruses are necessary to prevent the spread of transmission and future pandemics. Recently, studies on the detection of respiratory viruses have focused on electrochemical biosensors, especially for coronavirus disease 2019 (COVID-19), owing to their advantages such as low cost, fast response, and point-of-care applications. In this review, recent developments and applications of antibody-based, nucleic-acid-based, and aptamer-based biosensors for the electrochemical sensing of respiratory viruses from the years 2021 to 2023 are presented. Modification concepts and working principles of these biosensors are also demonstrated. In addition, the advantages and challenges of each biosensor and future prospects are discussed.
Keywords: electrochemical biosensor; respiratory virus; airborne; point-of-care; COVID-19; INFLUENZA-VIRUS; NUCLEIC-ACIDS; SARS-COV-2; ANTIBODIES; BIOSENSOR; APTAMER; IMMUNOSENSOR; PLATFORM; Instruments & Instrumentation; Materials Science